Man's Future in Arctic Areas. Proceedings of the 13th Polar Libraries Colloquy 10 - 14 June 1990 ... : PLC Proceedings 13 ... - Kivilahti, Raija; Kurppa, Liisa; Pretes, Michael (University of Alberta Library, 1990)
Papers presented at the 13th Polar Libraries Colloquy held June 10 - 14, 1990 at the Arctic Centre in Rovaniemi, Finland ...